Kualitas Pelayanan Administrasi Kependudukan Di Kelurahan Oetete Kecamatan Oebobo Kota Kupang - Takain, Brenadiva Rywanda; Toda, Hendrik; Rihi, David W. (Innovative: Journal Of Social Science Research, 2025)
This study aims to describe and analyze the Quality of Population Administration Services in Oetete Village, Oebobo District, Kupang City. Population Administration is needed by every community who wants to take care of letters. This research method uses descriptive analysis with a qualitative approach, namely research where the researcher tries to describe or describe the quality of Population Administration Services in Oetete Village, Oebobo District, Kupang City. Population Administration. Research results from five dimensions of Service Quality, namely: tangibles; seen from the physical facilities, room cleanliness, and employee appearance, empathy; individual attention and concern given by the company to customers, reliability; responsiveness; willingness to help customers quickly and responsively;assurance; The provision of a guarantee of non-defective products, shows that overall the Quality of Administrative Services at the Oetete Village Office is quite good even though from the aspects of empathy and realibility need to be improved. It can be concluded that the quality of Population Administration Services in Oetete Village, Oebobo District, Kupang City has not been implemented optimally in accordance with the expectations of the community.